upaya penyelesaian masalah risiko cedera pada ibu melalui pemberian telur ayam kampung untuk meningkatkan kadar hemoglobin ibu hamil trimester II - pertiwi, bekti mutia; Parmilah, Parmilah; Suraning Wulandari, Tri (JURNAL KESEHATAN KARTIKA, 2025)
Background: Anemia in pregnant women during the second trimester is one of the causes of increased risk of injury and complications during pregnancy. Non-pharmacological intervention efforts by providing high-iron foods, such as boiled eggs, are considered effective and easy to implement. Objective: The aim of the study is to determine the effect of consuming boiled eggs on the increase in hemoglobin levels in pregnant women during the second trimester with mild anemia. Method: The research method uses a case study of two pregnant women who experienced anemia with complaints of weakness, pale appearance, anemic conjunctiva, dizziness, and hemoglobin levels below 10.0 g/dL. The intervention was conducted by providing one boiled egg daily for seven days andbhemoglobin levels were measured using a tool easy touch. Results: The analysis showed that after the intervention for 7 days, with the frequency of giving one boiled egg each day, the hemoglobin levels of the pregnant women increased from 9.0 g/dL to 12.4 g/dL and from 9.4 g/dL to 14.4 g/dL. Conclusion: This finding indicates that the consumption of boiled chicken eggs has the potential to increase hemoglobin levels and can be an alternative simple, affordable, and safe nutritional intervention for pregnant women with anemia. It is recommended that health workers consider this approach in nutrition promotion and anemia prevention during pregnancy.